The Effect of Third Molars on the Mandibular Anterior Crowding Relapse—A Systematic Review - Ioannis Lyros; Georgios Vasoglou; Theodoros Lykogeorgos; Ioannis A. Tsolakis; Michael P. Maroulakos; Eleni Fora; Apostolos I. Tsolakis (Dentistry Journal, 2023)
The present systematic review updates the evidence on wisdom teeth contributing to lower incisor crowding following orthodontic treatment. Relevant literature was searched on online databases, namely Pubmed, Scopus, and Web of Science, up to December 2022. Eligibility criteria were formulated using the PICOS approach and PRISMA guidelines. Eligible research included original clinical studies involving patients previously being treated orthodontically with permanent dentition at the end of treatment, regardless of sex or age. The initial search yielded 605 citations. After considering eligibility criteria and removing duplicates, only 10 articles met the criteria for inclusion. The risk of bias of eligible studies was evaluated using the Cochrane Handbook for Systematic Reviews and Interventions tool. The majority were highly biased, mainly regarding allocation concealment, group similarity, and assessment blinding. The vast majority did not report statistically significant associations between the presence of third molars and crowding relapse. However, a minor effect has been suggested. Seemingly, there is no clear connection between mandibular third molars and incisor crowding after orthodontic treatment. The present review did not find adequate evidence to advocate preventative removal of the third molars for reasons of occlusal stability.